Suitability model and optimal location of biodigesters in the state of São Paulo - Paulino, Erik Júnior [UNESP]; Cherri, Adriana C. [UNESP]; Soler, Edilaine M. [UNESP] (Elsevier, 2024)
Growing concern over the environment has driven a search for renewable energy sources. Unlike the energy generated from fossil fuels, the energy from biomass is renewable, reducing the impact on the accumulation of carbon dioxide (CO2) in the atmosphere. Organic waste generated by agriculture, cities and industries are great sources of biomass for energy generation through biodigesters. Before starting the energy generation process, suitable locations are needed for the installation of bioenergy plants, bearing in mind that some locations have legal, environmental, economic and social restrictions. However, for this energy generation to be competitive, the plants must be installed in locations close to the biomass sources and the destinations of the energy generated. Few studies in the literature are directed to this logistical process. This paper describes a method developed in a Geographic Information System environment to classify the territory of São Paulo state as to its aptitude for the installation of bioenergy plants. In a second step, an optimization model was developed to represent the optimal allocation of plants in high aptitude locations. The number of plants and the optimal locations were determined to minimize the distances between the raw material and the plants and from the plants to the locations of generated energy demand. Simulations with different scenarios were used to verify the performance of the proposed method.
Keywords: Biodigesters; Bioenergy; Biogas; GIS; Operations research